(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
This essay entitled: Tourism dynamics of San Juan del Sur, Rivas in community leadership, refers to a series of direct and indirect practices influenced by different environments and my reflections on the concepts learned with Professor Luis Felipe Ulloa Forero in the Leadership Module II of the Master in Social Anthropology and Leadership, offered by the Department of Anthropology of the UNAN - Managua. The reflections are based on the information provided by the community actors that can be found in various fields, or in the Sectors with Interests at stake. (SIJUs) of the community of San Juan del Sur. All this under the influence of local, national, Latin American and global environments. Methodologically, observation and open interviews were conducted with the key settlers who validated these concepts. I think it is important to mention to the reader, that the essay is written in the first grammatical person since it was part of the suggestions on the part of Professor Ulloa, so that we would experience feeling responsible for what we perceive when researching and sharing when publishing.